Nurse’ Caring Behaviour Improve The Satisfaction of Patient’s Mother - Yuni Sufyanti Arief; Ertawati Ertawati; Durrotul Laili (Universitas Airlangga, 2009)
Introduction: Satisfaction of mother is the success indicator of nursing care in children ward. Most research show that nurses have a low motivation to provide on others caring behaviour. They pay more attention to curing. Thus most patient’s mother still not satisfied with the nurse care behavior. The aim of this study was to investigate correlation between nurse caring behaviour with satisfaction of patients’ mother in nursing care services.Method: A correlation study design was used in this study.There were 27 respondents who met the inclusion criteria. The independent variable was the nurse caring behavior and the dependent variable was satisfaction of patients’ mother. Data were collected by using questionnaire then analyzed by using Spearman Rank Correlation with significance level of α≤0.05. Result: The result showed that the nurse caring behaviour and the patients’ mother satisfaction had significance correlation (p=0.038). It can be concluded that nurse caring behaviour correlates to patient’s mother satisfaction in children ward. Discussion: Nurses should apply caring behavior for the patients and family to built patients’ mother satisfaction.